Advances in nuclear power process heat applications. - Khamis, I. (International Atomic Energy Agency, 2012)
"Following an IAEA coordinated research project, this publication compiles the findings of research and development activities related to practical nuclear process heat applications. An overview of current progress on high temperature gas cooled reactors coupling schemes for different process heat applications, such as hydrogen production and desalination, is included. The associated safety aspects are also highlighted. The summary report documents the results and conclusions of the project."--Provided by publisher.
"The IAEA officer responsible for this publication was I. Khamis of the division of nuclear power"--Foreword.
Keywords: Gas cooled reactors -- Design and construction.; Gas cooled reactors -- Safety measures.; Saline water conversion.; Hydrogen -- Research.; elektronické knihy; electronic books